The effectiveness of an interactive module in improving students' conceptual understanding of acid-base titration. (February 2020) - Desriana, D; Khaldun, I; Maulana, I; Habibati,; Ismayani, A
Abstract: The results of the previous studies showed that the implementation of acid-base titration module with interactive media which is based on computer technology can assist students to comprehend the concepts taught in the subject. In this study, the module with interactive media was delivered as an alternative in the real practicum for the material of acid-base titration. This study was conducted using a quantitative research method. The sample was collected by purposive sampling and divided into the experiment and control class. Data were analysed by the normalized gain (N-gain) while the student concept understanding data analysed by using percentage techniques. Data was collected through pre-test and post-test in both classes. Based on the result of N-gain average, the improvement of concept comprehension at the control class is 0.50 while it is 0.79 at the experiment class which is in the medium level. The hypothesis test of these two classes shows that the t-score (7.405) > t-table (1.996) with a significant level of 0.05. It can be concluded that there was a significant difference between control class and experimental class. The implementation of the module is effective in improving students' comprehension of the concept.